Sosialisasi Pengembangan Kelompok Sadar Wisata Berbasis Sapta Pesona Di Desa Aranio Kecamatan Aranio Kabupaten Banjar Provinsi Kalimantan Selatan - Mahyuni; Ismar Hamid; Evanrio Seanjaya; Muhammad Tifriji; Muhammad Hatni; Milda Rahmawati; Widya Wati Rohmatul Jannah; Norafifah; Ahmad Rusadi (Journal of Empowerment and Community Service (JECSR), 2021)
The tourism potential of the Flower River can be further developed if there is good management of structured tourism awareness groups under the supervision of the village government. In addition, the embodiment of Sapta Pesona (safe, orderly, clean, relaxed, beautiful, friendly, and memorable) in the Flower River creates a conducive and ideal environment for the development of tourism activities in a place. The purpose of the service is to increase public awareness to create an ideal Tourism Village based on 7 Sapta Pesona. The methodology used to develop the potential of this village is through the socialization of Awakening, the Sapta Pesona-Based Tourism Village, and the Development of Tourism Awareness Groups. From this activity, it will increase understanding of developing the tourism potential of Aranio Village, open up the insight of Flower River tourism managers so that they can plan programs that can rebuild Flower River tourism, the village government obtains the necessary reforms to revive tourist villages and can form legally aware tourism groups.